Co-design with Children: Using Participatory Design for Design Thinking and Social and Emotional Learning - Paracha Samiullah; Hall Lynne; Clawson Kathy; Mitsche Nicole; Jamil Fatima (De Gruyter, 2019)
This paper discusses leveraging design thinking techniques for involving children in serious game design in Japanese elementary schools. Our action research project approach accomplished two different goals: (1) to inculcate design thinking in pupils, and (2) to sensitize children on bullying victimization. Our approach uses a range of participatory design methods to distil design ideas from children and to support their design thinking aiming to boost children's creative confidence and develop social and emotional skills. Key findings from our project are: (1) children made valuable design contributions including realistic bullying scenarios, language content, user interface design, storyline progression, character profiles, coping strategies etc., and (2) participatory design and design thinking stimulated ethical reasoning, reflection and empathy in children on bullying victimization. Our approach is unique in the current design thinking landscape, because it moves from designing "thing" (object) to designing "think" (bullying sensitization). Future research should focus on highlighting ways how participatory design and design thinking enrich and complement each other. The significance of our paper stems from the simple standpoint that those participating in a design should gain from participating in the design process. Takeaways for practitioners are: (1) building relationships with stakeholders, especially children, (2) empathy and user research techniques, (2) translating field data into usable insights, (3) idea-generation and rapid concept development, (4) product co-prototyping, (5) user engagement and co-creation, (6) multiple perspectives on effective communication.